1968
DOI: 10.1177/070674376801300307
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five and Thirty-Five Year Follow up of First Admissions to Mental Hospital

Abstract: This has been a report of a study designed to assess the feasibility of long-term follow-up studies on Prince Edward Island. Cohorts of patients first admitted to the Island's only mental hospital during the early nineteen-thirties and early nineteen-forties were followed in retrospect in order to determine, a) the course and outcome of the major disorders over periods ranging up to thirty-five years and, b) the long-term effects of these disorders upon the families of the patients. Needed information was ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Five patients (11.6 %) stayed in hospital longer than 1 year on the first admission. Although this may seem an excessively long 21f initial hospitalization, it is much less than the figures for the 1930-40 period, when 60-65 % of schizophrenics were continuously hospitalized (Brown et al (1961), Beck (1968)), although by the 1960's only 10-13 % of British patients were retained more than 2 years (Brown (1959), MandeZbrote h Trick (1970)). Achte' (1967) reporting on two series of patients, from 1950 and 1960, gave mean lengths of stay on first admission of 121 and 148 days respectively.…”
Section: Use Of Servicesmentioning
confidence: 96%
“…Five patients (11.6 %) stayed in hospital longer than 1 year on the first admission. Although this may seem an excessively long 21f initial hospitalization, it is much less than the figures for the 1930-40 period, when 60-65 % of schizophrenics were continuously hospitalized (Brown et al (1961), Beck (1968)), although by the 1960's only 10-13 % of British patients were retained more than 2 years (Brown (1959), MandeZbrote h Trick (1970)). Achte' (1967) reporting on two series of patients, from 1950 and 1960, gave mean lengths of stay on first admission of 121 and 148 days respectively.…”
Section: Use Of Servicesmentioning
confidence: 96%
“…Although the duration of the follow-up period is evidently a crucial determinant of the outcome data, reported studies of outcome have varied from one (Johnstone et al 1979) to more than thirty years (Beck, 1968;Ciompi & Miiller, 1976). Clearly, comparison between such varied time spans is meaningless.…”
Section: Duration Of Follow-upmentioning
confidence: 99%
“…Few studies of the longterm course of schizophrenia have assessed clinical and social morbidity independently (Beck, 1968;Waxier, 1979;Salokangas, 1983), and fewer have employed standardized methods of diagnosis and outcome assessment (Tsuang & Winokur, 1975;Sartorius et al 1986), rendering the comparison of reported outcome hazardous. These are principally the unrepresentativeness of sampling; the lack of standardized diagnosis, with reliance on clinical records; and a lack of measurement of observer concordance and a lack of clear clinical and social criteria in the assessment of outcome.…”
Section: Six Recent Follow-up Studiesmentioning
confidence: 99%
See 1 more Smart Citation